Kloning Gen Penyandi Trehalosa Sintase dari Arthrobacter psychrolactophilus di Escherichia coli DH5-Alpha - Hendra Kusnadi; Nurul Izzati; Isa Nuryana; Fina Amreta Laksmi (BIOMARAS : Journal of Life Science and Technology, 2023)
Trehalose is a disaccharide sugar composed of two glucose molecules covalently linked. Trehalose plays a significant role in various industries as a stabilizer, preservative, sugar substitute, and protection against stress and dehydration conditions. Therefore, it is used in various industries including food, pharmaceutical, cosmetic, and biotechnology. Trehalose can be enzymatically produced from maltose using trehalose synthase enzyme (TreS, EC 5.4.99.16). This study aims to amplify the TreS gene from Arthrobacter psychrolactophilus bacterial isolate in Escherichia coli. The study started with the isolation of the TreS gene from the genome of Arthrobacter psychrolactophilus bacteria using PCR. Then, the base sequence confirmation was performed using sequencing methods. Subsequently, the cloning stage was carried out in E. coli DH5-?. The results of the study showed that the isolated TreS gene using PCR technique obtained a size of approximately 1439 bp, consistent with the expected size. The TreS gene did not undergo mutations based on the sequencing results using Clustal Omega tool, and the insert (pET28a-TreS) could be amplified, as indicated by the growth of E. coli DH5-? colonies on kanamycin selection medium. These results indicate that the TreS gene can be isolated using PCR technique and cloned in E. coli DH5-?. After confirming the successful cloning of the TreS gene, the next stage would involve the expression and characterization of the TreS gene.